Роль личностно-ориентированного обучения в формировании успешности студента - Куцын, Н. А. (НТУ "ХПИ", 2014)
Статья посвящена роли личностно-ориентированного обучения в формировании успешности личности. Показана роль создания ситуаций успеха, педагогики сотрудничества и других технологий в этом процессе.

The article is about discusses the role of student-centered learning in shaping the success of the individual. The role of creating situations of success, education cooperation and other technologies in the process.
Role of student-centered learning in formation achivment of student
Keywords: уверенность; становление личности; развитие; ситуация успеха; сотрудничество; активизация; success; self-confidence; development; establishment; cooperation; intensification